Experimental study on the selection of common adsorption substrates for extensive green roofs (EGRs) - Chen Xu (IWA Publishing, 2021)
Adsorption substrate in the substrate layer of an extensive green roof (EGR) is one of the most important factors affecting rainwater retention and pollution interception capacity. However, the contact time between runoff and adsorption substrate is extremely short in actual rainfall, and adsorption substrate cannot show fully rainwater retention and pollution interception capacity. So, selection of adsorption substrate based on its physical properties and theoretical adsorption capacity is unreliable. In this study, eight commonly-used adsorption substrate experimental devices are constructed with the same configuration. The delayed outflow time and runoff reduction rate of each device, along with event measurement concentration (EMC), average EMC, and cumulative pollutant quantity of SS, ammonium (NH4+), nitrate (NO3−), total nitrogen (TN), and total phosphorus (TP) in each device outflow under nine simulated rainfall events are measured and evaluated. The results indicate that vermiculite has a significant interception effect on NH4+ and TP with the advantages of low bulk density, high porosity, low cost, and a good rainfall runoff retention capacity under torrential rain and downpour events. In future practical engineering and related studies of EGR, attention should be paid to ameliorating the deficiencies of the adsorption substrates and optimizing their synergistic effects when combined with nutrient substrates.